Understanding the mechanism for the mechanical property degradation of a lithium disilicate glass-ceramic by annealing. (February 2018) - Li, D.; Li, X.C.; Zhang, Z.Z.; Zhang, S.F.; He, L.
Abstract: Post-crystallization annealing above the T g was applied to a lithium disilicate glass-ceramic with microstructure consisting of glassy matrix and rod-like lithium disilicate crystals, effect of the annealing on the mechanical behavior was investigated. Flexural strength and VIF toughness of the glass-ceramic unexpectedly decreased after the annealing. The mechanical behavior variation was understood based on residual micro-stress analysis. Coefficient of thermal expansion for the glassy matrix presented a tendency to increase after the annealing, which would enlarge the thermal expansion mismatch between the glassy matrix and the lithium disilicate crystals. As a result, the residual micro-stresses in the glass-ceramic abnormally increased with increasing the annealing time. The mechanical property degradation was attributed to the annealing-induced increase of the residual micro-stresses. Graphical abstract: Highlights: Post-crystallization annealing was applied to a lithium disilicate glass-ceramic. Mechanical property degradation of the glass-ceramic occurred after the annealing. The annealing induced residual micro-stress increase in the glass-ceramic. The mechanical property degradation was attributed to the residual stress increase.